Nilai-Nilai Buddhis Tentang Kesederhanaan dalam Menghadapi Gaya Hidup Konsumtif di Era Teknologi - Pani Nia Sari; Sentot; Aryanto Firnadi (Jounal Nyanadassana, 2025)
In this context, the values of simplicity in Buddhist teachings offer an alternative for living a more balanced and mindful life. This study aims to analyze Buddhist values of simplicity that are relevant to addressing consumerist lifestyles in the digital era and to describe their application in daily life. The method used is a literature study with a content analysis approach. Primary data were obtained from the Tripitaka scriptures, particularly the Vinaya Pitaka and Sutta Pitaka, while secondary data were sourced from books, journals, and other scientific literature. The results of the study show that Buddhist values of simplicity, such as contentment (santuṭṭhi), few desires (appiccha), self-restraint (indriya saṃvara), and minimalist living (na bahulika), are effective solutions to reduce consumerist behavior. These values foster inner balance, reduce dependence on external validation, and cultivate mindfulness in consumption decisions. In conclusion, Buddhist teachings on simplicity provide both practical and philosophical guidance for individuals to face consumerist lifestyles reinforced by technology, enabling a more peaceful, meaningful, and sustainable way of life.